2015
DOI: 10.1007/s00253-014-6364-5
|View full text |Cite
|
Sign up to set email alerts
|

Structural diversity and possible functional roles of free fatty acids of the novel soil isolate Streptomyces sp. NP10

Abstract: Herein, a novel soil bacterium Streptomyces sp. NP10 able to grow outside usual streptomycetes optimum conditions (e.g., at 4 °C, pH 9 and high NaCl concentration), exhibiting atypical hemolytic, DNAse, and cellulolytic activities, is described. This strain produces and excretes into the growth medium large amounts of free long-chain fatty acids (FAs). A concurrent lipidomics study revealed a large structural diversity of FAs with over 50 different n- and branched-chain, (un)saturated, and cyclopropane FAs (C7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
24
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 80 publications
(67 reference statements)
3
24
0
Order By: Relevance
“…The identification of these methyl esters was based on an analysis of their mass spectra and the comparison of the obtained RI data with the previously published ones for lower homologs from the series of n-, iso-and/or anteiso-long-chain fatty acids methyl esters. [16] Thus, in this way we proved the presence of hexyl esters of the above-mentioned branched iso-or anteiso-fatty acids (C 22 À C 31 ; Table 1) in the washings. Based on a detailed literature survey (Table S1), all identified hexyl esters of iso-or anteisofatty acids (8 constituents in total) represent new compounds and newly discovered natural products (Figure 1).…”
Section: Resultssupporting
confidence: 52%
“…The identification of these methyl esters was based on an analysis of their mass spectra and the comparison of the obtained RI data with the previously published ones for lower homologs from the series of n-, iso-and/or anteiso-long-chain fatty acids methyl esters. [16] Thus, in this way we proved the presence of hexyl esters of the above-mentioned branched iso-or anteiso-fatty acids (C 22 À C 31 ; Table 1) in the washings. Based on a detailed literature survey (Table S1), all identified hexyl esters of iso-or anteisofatty acids (8 constituents in total) represent new compounds and newly discovered natural products (Figure 1).…”
Section: Resultssupporting
confidence: 52%
“…Both SDS and these carboxylic acids have long hydrophobic alkyl tails and negatively charged head groups at pH 7. Interestingly, the NP10 strain of Streptomyces ( Figure 1A ) secretes carboxylic acids that have these characteristics ( Ilic-Tomic et al, 2015 ). We therefore used the tail drop assay to test a series of carboxylic acids of varying chain lengths, with and without cis double-bonds ( Figure 2C and Figure 2—figure supplement 1 ), to determine which, if any, C. elegans avoid.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, Streptomyces sp. NP10 strain was isolated, which is characterized by unusually high production of free fatty acids (FAs) (Ilic‐Tomic et al ., ). A lipidomics study on this strain revealed a large structural diversity of produced FAs with over 50 different n and branched chain, (un)saturated and cyclopropane FAs (C 7 –C 30 ).…”
Section: Mining Of Bacterial Genomes For New Bioactive Natural Productsmentioning
confidence: 97%
“…A lipidomics study on this strain revealed a large structural diversity of produced FAs with over 50 different n and branched chain, (un)saturated and cyclopropane FAs (C 7 –C 30 ). Two of these, i ‐17:0cy9‐10 and a ‐18:0cy9‐10, represent new natural products (Ilic‐Tomic et al ., ). Based on the genome analysis of this strain coupled to gene inactivation, our group successfully identified a unique FA biosynthesis gene cluster responsible for this particular phenotype (Schneider et al ., ).…”
Section: Mining Of Bacterial Genomes For New Bioactive Natural Productsmentioning
confidence: 97%